(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2025)
Diabetes mellitus is a condition where blood sugar levels become high due to insulin deficiency or resistance. One effort to control blood sugar levels is to eat foods low in sugar and carbohydrates. Ice cream with low sugar ingredients and a low glycemic index such as kapok banana flour, porang flour and soy milk can be an alternative product that is suitable for consumption by diabetes sufferers. This research objective was to analyze the sensory quality characteristics and nutritional content of ice products based on kapok banana flour and porang flour. This research uses an experimental study design with an experimental plan, namely a Completely Randomized Design. This research was carried out in three stages, namely the formulation process, organoleptic and proximate tests, sugar and fiber content. This research used 35 semi-trained panelists, namely students from the Bachelor of Nutrition Study Program, FKK UMJ. Research was conducted at the Sensory Laboratory, Faculty of Medicine and Health, Universitas Muhammadiyah, Jakarta. Statistical tests use the Kruskal Wallis test and further tests use Mann Whitney. The research results show that based on the hedonic quality test, there are real differences in color, aroma, taste, texture in the characteristics of ice cream. Meanwhile, based on the results of the hedonic test, there were real differences in the taste and texture of the ice cream. The best formula was chosen using the exponential comparison method (MPE), namely F2. Based on the results of nutritional content tests, it shows that ice cream products have an energy content of 98 kcal per 100 g. The total sugar content is 2.49% and dietary fiber 3.32%. The carbohydrate, protein, fat and total sugar content in the selected formula does not yet meet SNI Ice Cream 01-3713-1995 and the nutritional content requirements of PKMK for diabetics. Meanwhile, the dietary fiber component is above the PKMK nutritional content requirements for people with diabetes.